Interleukin-4 Inhibits Regulatory T Cell Differentiation through Regulating CD103+ Dendritic Cells - Tu, Lei; Chen, Jie; Zhang, Hongwei; Duan, Lihua (Frontiers in Immunology, 2017)
CD103+ dendritic cells (DCs) have been shown to play a crucial role in the pathogenesis of inflammatory bowel diseases (IBDs) through educating regulatory T (Treg) cells differentiation. However, the mechanism of CD103+ DCs subsets differentiation remains elusive. Interleukin (IL)-4 is a pleiotropic cytokine that is upregulated in certain types of inflammation, including IBDs and especially ulcerative colitis (UC). However, the precise role of IL-4 in the differentiation of CD103+ DCs subpopulation remains unknown. In this study, we observed a repressive role of IL-4 on the CD103+ DCs differentiation in both mouse and human. High dose IL-4 inhibited the CD103+ DC differentiation. In comparison to CD103- DCs, CD103+ DCs expressed high levels of the co-stimulatory molecules and indoleamine 2,3-dioxygenase (IDO). Interestingly, IL-4 diminished IDO expression on DCs in a dose-dependent manner. Besides, High dose IL-4-induced bone marrow-derived DCs (BMDCs) and monocyte-derived DCs (MoDCs) revealed mature DCs profiles, characterized by increased co-stimulatory molecules and decreased pinocytotic function. Furthermore, DCs generated under low concentrations of IL-4 favored Tregs differentiation, which depend upon IDO produced by CD103+ DCs. Consistently, IL-4 also reduced the frequency of CD103+ DC in vivo. Thus, we here demonstrated that the cytokine IL-4 involved in certain types of inflammatory diseases by orchestrating the functional phenotype of CD103+ DCs subsets.